2005
DOI: 10.1016/j.ijgo.2005.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment levels of serum squamous cell carcinoma antigen and urine polyamines in women with squamous cell carcinoma of the cervix

Abstract: Pretreatment measurement of SCCA and urine polyamine levels may help in predicting lymph node metastases in women with early stage cervical carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Kim[ 18 ] explored the predicting value of SCCA on lymph node metastases in 104 patients with early stage (IB-IIA) cervical carcinoma. It was found that patients with positive nodal involvement has the SCCa 3.9ng/ml while the negative node has 1.1ng/ml.…”
Section: Resultsmentioning
confidence: 99%
“…Kim[ 18 ] explored the predicting value of SCCA on lymph node metastases in 104 patients with early stage (IB-IIA) cervical carcinoma. It was found that patients with positive nodal involvement has the SCCa 3.9ng/ml while the negative node has 1.1ng/ml.…”
Section: Resultsmentioning
confidence: 99%
“…SCCA is commonly used to assist in the diagnosis and surveillance of squamous cell cancers, and serum concentration of SCCA is elevated in 28 - 88% of patients with SCC [ 22 , 23 ]. Compared to patients without lymph node metastasis, SCCA levels before treatment were higher in patients with lymph node metastasis [ 24 ]. In a previous study by Bolger et al , when pretreatment SCCA level was > 2, > 4, and > 8.6 ng/ml, the positive predictive value for lymph node metastasis was 51.4%, 70.0%, and 100%, with sensitivities of 58.1%, 45.2%, and 22.6%, respectively [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Torre et al [ 40 ] also indicated that serum SCC-Ag was elevated in patients with benign conditions including tuberculosis, eczema, and pemphigus. Kim et al [ 41 ] demonstrated that increased serum SCC-Ag (>2.0 ng/mL) may be predictive for lymph node metastases in early-stage cervical carcinoma, and Takeda et al [ 42 ] reported that serum SCC-Ag levels over 1.5 ng/ml were significantly associated with lymph node metastasis. However, the cutoff levels for SCC-Ag varied from study to study resulting in vastly different sensitivity and specificity values for this marker [ 34 , 43 , 44 ], and a normal pretreatment SCC-Ag level does exclude the presence of lymph node metastases in cervical cancer [ 45 ].…”
Section: Discussionmentioning
confidence: 99%